The CINRG Becker Natural History Study: Baseline characteristics. Issue 3 (24th July 2020) - Clemens, Paula R.; Niizawa, Gabriela; Feng, Jia; Florence, Julaine; DʼAlessandro, Andrea Smith; Morgenroth, Lauren P.; Gorni, Ksenija; Guglieri, Michela; Connolly, Anne; Wicklund, Matthew; Bertorini, Tulio; Mah, Jean K.; et al.
Abstract: We performed an observational, natural history study of males with in‐frame dystrophin gene deletions causing Becker muscular dystrophy (BMD). A prospective natural history study collected longitudinal medical, strength, and timed function assessments. Eighty‐three participants with genetically confirmed BMD were enrolled (age range 5.6–75.4 years). Lower extremity function and the percentage of participants who retained ambulation declined across the age span. The largest single group of participants had in‐frame deletions that corresponded to an out‐of‐frame deletion treated with an exon 45 skip to restore the reading frame. This group of 54 participants showed similarities in baseline motor functional assessments when compared to the group of all others in the study. A prospective natural history cohort with in‐frame dystrophin gene deletions offers the potential to contribute to clinical trial readiness for BMD and to analyze therapeutic benefit of exon skipping for Duchenne muscular dystrophy.